Orlicz difference bodies - Shi Wei; Wang Weidong; Ma Tongyi (Open Mathematics, 2018)
In this paper, by the Orlicz-Minkowski combinations of convex bodies, we define the general Orlicz difference bodies and study their properties. Furthermore, we obtain the extreme values of the general Orlicz difference bodies and their polars.